Olympic weightlifting training improves vertical jump height in sportspeople: a systematic review with meta-analysis. Issue 14 (30th November 2015) - Hackett, Daniel; Davies, Tim; Soomro, Najeebullah; Halaki, Mark
Abstract : Purpose: This systematic review was conducted to evaluate the effect of Olympic weightlifting (OW) on vertical jump (VJ) height compared to a control condition, traditional resistance training and plyometric training. Methods: Five electronic databases were searched using terms related to OW and VJ. Studies needed to include at least one OW exercise, an intervention lasting ≥6 weeks; a comparison group of control, traditional resistance training or plyometric training; and to have measured VJ height. The methodological quality of studies was assessed using the Downs and Black Checklist. Random and fixed effects meta-analyses were performed to pool the results of the included studies and generate a weighted mean effect size (ES). Results: Six studies (seven articles) were included in the meta-analyses and described a total of 232 participants (175 athletes and 57 physical education students) with resistance training experience, aged 19.5±2.2 years. Three studies compared OW versus control; four studies compared OW versus traditional resistance training; and three studies compared OW versus plyometric training. Meta-analyses indicated OW improved VJ height by 7.7% (95% CI 3.4 to 5.4 cm) compared to control (ES=0.62, p=0.03) and by 5.1% (95% CI 2.2 to 3.0 cm) compared to traditional resistance training (ES=0.64 p=0.00004). Change in VJ height was not different for OW versus plyometric training. Conclusions: OW is an effective training method to improve VJ height. The similar effects observed for OW and plyometric training on VJ height suggests that either of these methods would be beneficial when devising training programmes to improve VJ height.